The Role of the Church in Low-Income Housing in Namibia - Khiba, Ritta; Ntlhe, Daphne (International Journal of Social Science and Religion (IJSSR), 2024)
The paper examines the church's role in Namibia's low-income housing process. The study followed the qualitative method; data were drawn from journals, books, newspapers, and other relevant material. The article argues that the church in Namibia plays a positive role in low-income housing and promotes Sustainable Development Goals. The findings reveal that the church established a foundation for the current Shack Dwellers Federation of Namibia, an umbrella body of savings groups that address housing issues for low-income groups. The church plays a significant role by building houses for the poor, donating materials, and helping low-income communities alleviate poverty. The study supports participatory planning efforts in housing, highlighting that the church and faith-based organizations have a place in promoting Sustainable Development Goals, particularly goals 1, 2, and 11. It augments literature in religious studies, the built environment, and sustainable urban development by investigating the church's role in housing provision. In contrast, most studies focus on the church’s involvement in politics, culture, and socio-economic development. The study will benefit stakeholders who want to contribute towards goal 11 (Sustainable cities and communities). Additionally, the contribution will grow as the research serves as a novel contemporary reference for future studies in the same field.